Experimental investigation of a spiral tube embedded latent thermal energy storage tank using paraffin as PCM - Zhang, Siming (2018)
Latent thermal energy storage (LTES) is widely used in excess energy reservation. The performance of a LTES unit is critical for its application. In this study, the spiral tube embedded LTES tank is investigated experimentally, with a composite of paraffin as the phase change material (PCM). Temperature distribution of PCM in the tank was obtained, for both charging and discharging processes. The results showed that during the charging process, the temperature of upper part of PCM increases faster than that in the lower part, which is considered as the effect of natural convection of PCM that dominates the charging process. Inlet water temperature has a greater influence rather than flow rate on heat transfer performance since the increase of temperature difference between HTF and PCM reduces all thermal resistance in the heat transfer, however it could not be increased infinitely to enhance heat transfer performance.